Model penuntasan Pendidikan Dasar Sembilan Tahun usulan daerah - Sukarno, Makmuri (Jurnal Kependudukan Indonesia, 2012)
One of the strategies to break the chain of poverty is to enhance the education of the population, which can be done, among other things, by completing the Nine-Year Compulsory Education. This paper is departed from a 2010 research and conducted in three regions: Wonosobo, Ciamis, and South Minahasa. It tries to illustrate the proposals offered by the regions' stakeholders in the attempt to enhance the education of the population, particularly in the execution of primary education. This paper also contains discussions related to problems/barriers that were faced by the regions in order to implement the completion of the primary education program according to three main stakeholders: the community, the government, and the businesses. The data source for this study discussion was excavated from the in-depth interview method. Secondly ,this paper discusses proposals from the three stakeholders to penetrate the barriers of the program that were formulated from perspectives of each region and were based on data sources excavated from the collective assessment method. From the two points above, it appears that the composition of the educational content, the financing scheme, and the stakeholders' configuration that were proposed by the stakeholders in the three regions were in fact different from the model that is now being used.